1996
DOI: 10.1302/0301-620x.78b5.0780722
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative Changes at the Knee and Ankle Related to Malunion of Tibial Fractures

Abstract: W e re-examined clinically and radiologically 88 patients with a fracture of the lower leg at a mean follow-up of 15 years. Forty-three fractures (49%) had healed with malalignment of at least 5°. More arthritis was found in the knee and ankle adjacent to the fracture than in the comparable joints of the uninjured leg. Malaligned fractures showed significantly more degenerative changes.Eighteen patients (20%) had symptoms in the fractured leg. There was a significant correlation between symptoms in the knee an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(68 citation statements)
references
References 13 publications
1
62
0
5
Order By: Relevance
“…This observation conforms to clinical literature that lists OA as a common fracture complication (Anderson et al 2011). Small sample sizes prohibited description of the distribution of OA by sex, but the fact that the observable joint surfaces of fractures with deformity (i.e., linear and/or rotation) greater than 15 degrees all exhibit OA, provides further evidence to support the post-traumatic development of this condition in bones that have healed with deformities (Van Der Schoot et al 1996).…”
Section: Healing and Treatmentsupporting
confidence: 83%
See 1 more Smart Citation
“…This observation conforms to clinical literature that lists OA as a common fracture complication (Anderson et al 2011). Small sample sizes prohibited description of the distribution of OA by sex, but the fact that the observable joint surfaces of fractures with deformity (i.e., linear and/or rotation) greater than 15 degrees all exhibit OA, provides further evidence to support the post-traumatic development of this condition in bones that have healed with deformities (Van Der Schoot et al 1996).…”
Section: Healing and Treatmentsupporting
confidence: 83%
“…Mal-union is typically indicative of failed or lack of treatment and can result in a variety of consequences, including the development of secondary osteoarthritis, dysfunction, and pain (Karnezis et al 2005;Van Der Schoot et al 1996). To assess unsuccessful fracture healing in the past, a model suggested by Roberts (1988a) used radiographs and patient records of living British people with conservatively treated (i.e.…”
Section: Fracture Recording and Radiographymentioning
confidence: 99%
“…In patients with more than 5° of malalignment, it is observed that the complaints and degeneration in the ankle are increased, [30] and this is suggested to be the result of increased contact at any point of the ankle joint. [30][31][32][33] We used the AOFAS scale in order to clinically evaluate the consistent ankle pain and early osteoarthritis in our cases. When the scores of the intramedullary nailing and plate fixation groups were compared, a statistical significance was found, and the results were good or perfect.…”
Section: Discussionmentioning
confidence: 99%
“…So leiden Patienten unter Gangbildstörungen mit dauerhaftem Hinken, chronischen Schmerzen in Hüft-und Kniegelenken sowie schmerzhaften Seitenbandreizungen. Nach fehlverheilten Tibiaschaftfrakturen wurde ferner ein frühzeitiger Gelenkverschleiß im langfristigen Verlauf nachgewiesen [25,31]. Allgemein gilt, dass eine vermehrte Innentorsionsabweichung schlechter toleriert wird und eher zu Beschwerden führt als eine Außentor-sionsabweichung.…”
Section: Anwendungsgebiete Und Bisherige Erfahrungenunclassified